Fortification of Date Bars with Different Protein Sources and their Nutritional Profiling: Nutritional Value of Date Bars (Biological Sciences - PJSIR, 2022)
Date bar is an energy-dense snack food with a high content of carbohydrates and bioactive compounds and deficits protein. The date bar can be fortified with different protein sources and may be used as a functional food product to overcome protein related malnutrition. The present study was conducted to develop protein fortified date bars using skim milk, soybean and almond powders as protein sources and to examine their physico-chemical and sensory characteristics. Four different treatments for protein fortified date bar samples were prepared with different formulations and coded as A (control, 100% date fruit), B (80% date fruit + 20% skim milk powder), C (80% date fruit + 20% soybean powder) and D (80% date fruit + 20% almond powder). Among the treatments, D and C were found to have significantly higher (P